(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Crystallography is the study of crystals and their formation or determination of atom patterns in solid crystals. In the past, devices like goniometers were used for gaining information about crystal structures, but study of inner crystal structures became possible with Rontegin`s discovery of x-rays, which created x-ray crystallography. X-ray crystallography is the study of the determination of the atomic and molecular structure of crystals, whose crystal structure causes x-ray-emitted waves to diffract or divide. By measuring the angle and intensity of these diffracted waves, we can obtain the shape and size of a unit cell and a 3D photo of the electron density of crystals. This 3D photo of the electron density of crystals shows the location of electrons in crystal atoms. X-ray crystallography is a base for finding functions of biological molecules like vitamins, drugs, proteins, and nucleic acids.